Australian Economic History: Transformations of an Interdisciplinary Field - Claire E. F. Wright (ANU Press, 2022)
In a time of pandemics, war and climate change, fostering knowledge that transcends disciplinary boundaries is more important than ever. Economic history is one of the world's oldest interdisciplinary fields, with its prosperity dependent on connection and relevance to disciplinary behemoths economics and history. Australian Economic History is the first history of an interdisciplinary field in Australia, and the first to set the field's progress within the structures of Australian universities. It highlights the lived experience of doing interdisciplinary research, and how scholars have navigated the opportunities and challenges of this form of knowledge. These lessons are vital for those seeking to develop robust interdisciplinary conversations now and in the future.
Keywords: 330; Interdisciplinary research; Australian history of education; Australian economic history; University policy